Book review: Right from the Start: Investing in parents and babies, CCWB Press, ISBN: 978-0-9933527-6-8 - Mike Findlay (Scottish Journal of Residential Child Care)
It is widely accepted that the earliest months and years of a child's existence have the most profound impact on the rest of the life. Attachment theorists believe that the early bonds and relationships that a child forms with his or her carer(s) or parent(s), informs that child's ability or inability to form successful and healthy relationships in the future. Alan Sinclair's Right from the Start is the latest in the Postcards from Scotland series of short books, which aim to stimulate new and fresh thinking about why us Scots are the way we are.